2024
DOI: 10.3389/fphar.2023.1272091
|View full text |Cite
|
Sign up to set email alerts
|

A minimal PBPK model to accelerate preclinical development of drugs against tuberculosis

Federico Reali,
Anna Fochesato,
Chanchala Kaddi
et al.

Abstract: Introduction: Understanding drug exposure at disease target sites is pivotal to profiling new drug candidates in terms of tolerability and efficacy. Such quantification is particularly tedious for anti-tuberculosis (TB) compounds as the heterogeneous pulmonary microenvironment due to the infection may alter lung permeability and affect drug disposition. Murine models have been a longstanding support in TB research so far and are here used as human surrogates to unveil the distribution of several anti-TB compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The authors concluded that both plasma and lung PK profiles were well summarized by AUC and C max values. 29 Hence, in our analysis, these measures were used as metrics of model performance for extrapolation purposes together with visual inspection of concentration–time profiles.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that both plasma and lung PK profiles were well summarized by AUC and C max values. 29 Hence, in our analysis, these measures were used as metrics of model performance for extrapolation purposes together with visual inspection of concentration–time profiles.…”
Section: Methodsmentioning
confidence: 99%
“…To compare the results obtained from these selected compounds, 4 reference inhibitors against DprE1 were selected from the literature: BTZ043, OPC_167832, TBA_7371, and PBTBZ169. 22 - 25 …”
Section: Methodsmentioning
confidence: 99%
“…stormTB implements the minimal physiologically based pharmacokinetics model (mPBPK) presented by (Reali et al, 2024) that describes the disposition of 11 anti-pulmonary-TB drugs in murine models. The supported drugs are rifampicin (RIF, R), rifapentine (RPT, P), pyrazinamide (PZA, Z), ethambutol (EMB, E), isoniazid (INH, H), moxifloxacin (MOX, M), delamanid (DEL), pretomanid (PRE, Pa), bedaquiline (BDQ, B), Quabodepistat (QBS, OPC-167832), and GSK2556286 (G286).…”
Section: Minimal-pbpk Modelmentioning
confidence: 99%
“…Here, we present a web-based tool tailored for anti-TB drug dynamics and PK/PD metrics in the treatment scenarios to support model-informed treatment development under a unified perspective. It leverages a previously published minimal physiologically based pharmacokinetic (mPBPK) model that supports 11 historical and under-development anti-TB drugs in a common pre-clinical murine model (Reali et al, 2024). We have then consolidated the results from model calibration and virtual population-based uncertainty quantification in the herein introduced R-based web app, stormTB, streamlining model inspection and enabling users to conduct independent what-if analyses using the mPBPK platform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation